Crystal structure and magnetic properties of a linear tetranuclear CoII cluster. Issue 9 (26th August 2016) - Wang, Yingying; Wen, Meixia; Gao, Zhongjun; Sheng, Ning
Abstract : A linear tetranuclear unit, in which the two Co II ions at the ends are six‐coordinated and the two inner Co II ions are five‐coordinated in a distorted triangular bipyramidal configuration, is the first example of ( E )‐2‐[(2‐hydroxybenzylidene)amino]phenol in coordination chemistry co‐operating with 1, 10‐phenanthroline under solvothermal conditions. Magnetic studies show the presence of ferromagnetic Co II …Co II exchange interactions in the tetranuclear unit. Abstract : Polynuclear complexes are an important class of inorganic functional materials and are of interest particularly for their applications in molecular magnets. Multidentate chelating ligands play an important role in the design and syntheses of polynuclear metal clusters. A novel linear tetranuclear Co II cluster, namely bisμ3 ‐( E )‐2‐[(2‐oxidobenzylidene)amino]phenolatobisμ2 ‐( E )‐2‐[(2‐oxidobenzylidene)amino]phenolatobis(1, 10‐phenanthroline)tetracobalt(II), [Co4 (C14 H11 NO2 )4 (C12 H8 N2 )2 ], was prepared under solvothermal conditions through a mixed‐ligand synthetic strategy. The structure was determined by X‐ray single‐crystal diffraction and bulk purity was confirmed by powder X‐ray diffraction. The complex molecule has a centrosymmetric tetranuclear chain‐like structure and the four Co II ions are located in two different coordination environments. The Co II ions at the ends of the chain are in a slightly distorted octahedral geometry, while the two inner Co II ions are in five‐coordinate distorted trigonal bipyramidal environments. A magnetic study reveals ferromagnetic Co II …Co II exchange interactions for the complex.